3-Phase Full Bridge Converter Based SRM for Closed Loop Control of an Electric Vehicle - et. al., K. Akhila Reddy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper a SRM is operated using different control circuits which include a) AHBC b) AFBC c) AHBC with closed loop control. In all the control modules the machine used is the same three phase 6/4 SRM machine. A performance analysis is carried out on SRM with these different circuits and the analysis is compared for best performance module selection. The modeling of these proposed modules is designed in MATLAB Simulink software for result validation with generation of graphs using ‘powergui’ toolbox. The plotted graphs for the comparison are always with respect to time.